Small-Molecule Inhibitors at the PSD-95/nNOS Interface have Antidepressant-Like Properties in Mice. - Harkin, Andrew; Dev, Kumlesh (My University, 2013)
Previous studies have demonstrated that nitric oxide (NO) synthase inhibitors are as efficacious as tricyclic antidepressants in preclinical antidepressant screening procedures and in attenuating behavioural deficits associated with animal models of depression. TheN-methyl-D-aspartate receptor (NMDA-R) complex gates Ca2þ, which interacts with calmodulin to subsequently activate NO synthase. We hypothesised that uncoupling neuronal nitric oxide synthase (nNOS) from the NMDA-R through the scaffolding protein post synapticdensity protein 95 (PSD-95) would produce behavioural antidepressant effects similar to NO synthase inhibitors. Small-moleculeinhibitors of the PSD-95/nNOS interaction, IC87201 (0.01–2 mg/kg) and ZL006 (10 mg/kg) were tested for antidepressant properties in tests of antidepressant activity namely the tail suspension and forced swim tests in mice. We now report that IC87201 and ZL006produce antidepressant-like responses in the forced swimming test (FST) and tail suspension test (TST) following a single administration in mice. By contrast to the tricyclic antidepressant imipramine (25 mg/kg), the effects are not observed 1 h following drug administration but are apparent 24 and 72 h later. Furthermore prior exposure to the TST or FST is required in order to observe the antidepressant-related activity. Similar delayed and sustained antidepressant-like effects were observed following TRIM (50 mg/kg) and ketamine(30 mg/kg) in the TST. The antidepressant-like effects of ZL006 also generalise to IC87201 in the TST. IC87201 was devoid of effects on locomotor activity and step-through latency in the passive avoidance cognition test. These data support the hypothesis that targeting thePSD-95/n NOS interaction downstream of NMDA-R produces antidepressant effects and may represent a novel class of therapeutics for major depressive disorders.
PUBLISHED
Keywords: Nitric oxide synthase; N-methyl-D-aspartate receptor; IC87201; Antidepressant; Tail suspension test; Mouse